2020
DOI: 10.1186/s12913-020-05719-z
|View full text |Cite
|
Sign up to set email alerts
|

Lowered blood pressure targets identify new, uncontrolled hypertensive cases: patient characteristics and implications for services in Thailand

Abstract: Background According to the new hypertension treatment guidelines blood pressure (BP) readings need to be kept below or equal to 130/80 mmHg in patients aged less than 65 years old. This study shows the change in proportion of identified cases of uncontrolled blood pressure in light of these changes. Methods The data was collected from 248 hypertensive patients who had visited an outpatient clinic at the Department of Family Medicine, Faculty of Medicine, Chiang Mai University, Thailand. Patients were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Our findings are in‐line with previous studies where CCBs are the most commonly used antihypertensive medication, while diuretics are less commonly used. 14 , 19 , 20 This is likely due to the 2011 Asian Pacific Heart Associations’ recommendation for CCBs to be the preferred drug for managing hypertension in East Asian countries, 21 while the use of diuresis is usually avoided due to the expected problems with diuresis and the need to monitor serum potassium. This is also reflected in our result where only about one‐third had their serum potassium assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in‐line with previous studies where CCBs are the most commonly used antihypertensive medication, while diuretics are less commonly used. 14 , 19 , 20 This is likely due to the 2011 Asian Pacific Heart Associations’ recommendation for CCBs to be the preferred drug for managing hypertension in East Asian countries, 21 while the use of diuresis is usually avoided due to the expected problems with diuresis and the need to monitor serum potassium. This is also reflected in our result where only about one‐third had their serum potassium assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found dose adjustment to be especially important for hypertension control, but other factors may be considered to improve the overall hypertension control rates in Thailand. 20 Literature suggests that suboptimal control usually reflect existing programmatic challenges including suboptimal management, long waiting times for consultation and drug collection which encourage loss to follow‐up. 35 , 36 Reorganization services to include a multidisciplinary care team may be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The translation of the questionnaire followed the WHO suggested standard procedure. The validation study has not been performed for the Thai language but has been used in published research [ 22 ]. Factor analysis was performed and the factor loadings of all MGL items ranged from 0.54 to 0.74 (>0.4).…”
Section: Methodsmentioning
confidence: 99%